Features of distribution and ecology of the brown bear (Ursus arctos) in the Carpathian National Park (Ukraine) - Oleksandr Kyseliuk; Bohdanna Kalynchuk; Yurii Motruk (Theriologia Ukrainica)
The distribution and some ecological features of the brown bear (Ursus arctos) in the Carpathian National Nature Park (CNNP) in 2019–2023 are considered. The study is based on field observations and analysis of camera trap data collected by the inspectors of the park’s departments and the employees of the scientific department. In particular, 157 cases of bear activity and presence were recorded, of which three cases were captured by camera traps. The results show that the brown bear prefers middle-aged spruce and fir plantations (38.7%). Bear tracks are also frequently found in middle-aged stands with dense crown closure (26.5 %), which may indicate the importance of dense forests for bears. This may be due to the fact that such forests provide sufficient food and shelter for bears. A smaller number of cases are occurrences in young and maturing stands. This may be due to the fact that such stands have not yet reached the optimal structure to meet the needs of bears. The lowest number of cases was found in pastures and hayfields. The maximum altitude at which a bear was recorded was 1696 m, and the minimum was 745 m. The highest number of observations was recorded at altitudes of 900–1000 m (31.2%), and the lowest at altitudes of 700–800 m (3.18%). According to the authors, this is due to the fact that there are no settlements at higher altitudes and the disturbance factor of animals is lower. The distribution and places of occurrence of this species in the park over the past five years are analysed. The number of bears has increased in recent years. This is obviously due to a decrease in human impact (coronavirus restrictions, martial law, and the absence of poaching). Currently, there are up to 20 bear individuals in the park. The exact number of bears is difficult to determine due to double counting and lack of coordination between neighbouring forestry enterprises and protected areas. The data presented here are important for the development of conservation strategies for the brown bear, as they allow the most favourable environments to be identified and measures for the protection and management of the park’s territory to be planned.